DEPRESSION AND ANXIETY FOLLOWING EARLY PREGNANCY LOSS – OCCURRENCE AND RISK FACTORS - Skeparovska, Kristina; Ilkoski, Ana; Biljan, Aleksandra; Drogrishki, Marta; Simonovska, Biljana; Mitrovska, Stefanija (Journal of Morphological Sciences; Vol 6 No 2 (2023): JMS, 2023)
Early pregnancy loss is associated with various psychological symptoms shortly after the miscarriage which, in some patients, can persist a longer period of time. The main goal of our study is to establish the occurrence-rate and risk factors for development of these symptoms. Patients with early pregnancy lose, who came in hospital were enrolled in the study. The HADS (Hospital Anxiety and Depression Scale) was used to measure symptoms of depression and/or anxiety of these patients. Chi-square test was used for statistical analysis. Out of total 70 patients, 60% reported symptoms of depression and/or anxiety at some point during the study. Half of them, i.e. 54.2% display the symptoms on the day of admission to the hospital, while 9.5% of the patients demonstrated onset of symptoms of depression and/or anxiety one month after the incident. The symptoms persisted at least one month following the miscarriage, in 64.3% of the patients. Regarding the studied variables (nationality, level of education, employment and marital status as well as number of previous pregnancy loss and the number of children), none of them shows statistically significant difference for developing symptoms of depression and/or anxiety. 60% of women display symptoms of anxiety or/and depression following early pregnancy loss, majority of them immediate after the incident, so every hospital should be well-staffed by professionals and able to provide an adequate care and psychological support for these patients. The study failed to reveal any risk factor (among selected) significantly associated with development of symptoms of depression and anxiety. Hence, every woman with such diagnosis can potentially develop psychological stress, and should be monitored carefully. Keywords: anxiety, depression, early pregnancyloss, HADS.